Physicians’ and nurses’ experience of using the Abbey Pain Scale (APS) in people with advanced cancer: a qualitative content analysis - Tegenborg, Sussi; Fransson, Per; Martinsson, Lisa (BMC Nursing, 2023)
The Abbey Pain Scale (APS), an observational scale used to assess pain in people with end-stage dementia, is also widely used in Sweden to assess pain in patients with advanced cancer. It is unclear whether the APS is appropriate in this context. This study aims to explore physicians’ and nurses’ experiences of using a Swedish translation of the APS (the APS-SE) in people with advanced cancer.
Keywords: Abbey Pain Scale; Cancer; End-of-life care; Pain assessment; Palliative care; Qualitative content analysis